Utilização do enfoque CTS em cursos de engenharia com vistas à formação cidadã - Pinto, Valdir Rogério Corrêa (2019)
This research aimed to investigate advances in the process of training engineers, based on Problem Methodology and the implementation of didactic-methodological methods that provide debates and reflections, touching a citizen and humanistic formation focused on Science, Technology and Society (STS). How to participate in a technical subject in the field of hydraulics in engineering courses, involving the contents "Open Channels" and "Water Distribution", and a thematic approach focused on the development of projects based on real problems, students study. Eighteen students from the 6th year of the Environmental and Sanitary Engineering course and 61 students from the 8th year of the Civil Engineering course belonging to the Nossa Senhora do Patrocínio University Center (CEUNSP), at the Salto / SP campus, participated in the research. Based on legal documents and compared on the assumptions of the STS movement, one proposal sought to develop skills for the conscious exercise of citizenship, directing technical and scientific knowledge beyond university boundaries. Thus, it increases the students' capacity for critical and reflexive thinking, contributing to the formation of a professional able to face the current challenges in the field of Engineering. The results showed a transformative character, as future professionals acquired greater concern and awareness about the need to analyze and develop projects based on not only technical and economic aspects, but also aiming at social welfare, respect for environment, and better quality of life. Students were able to develop values and attitudes, improving their vision of personal and professional reality, favoring decision-making processes that consider possible impacts on society and the environment, objective of the STS approach.